Case Report: Identification of a novel CASK missense variant in a Chinese family with MICPCH - Zhang, Runfeng; Jia, Peng; Yao, Yanyi; Zhu, Feng (Frontiers in Genetics, 2022)
Mental retardation and microcephaly with pontine and cerebellar hypoplasia (MICPCH) is a rare genetic disorder that results in varying levels of pontocerebellar hypoplasia, microcephaly, and severe intellectual disabilities. Prior genetic analyses have identified the CASK gene as a driver of MICPCH. Herein, we analyzed a Chinese family with MICPCH. The index patient was an 8-year-old male. He and his 3-year-old brother suffered from microcephaly, pontocerebellar hypoplasia, serious mental retardation, ataxia, gait disorder, and inability to speak. Through a combination of whole-exome sequencing and subsequent Sanger sequencing, a novel X-linked missense mutation, c.1882G>C (p.D628H) in the CASK gene, was identified in two siblings, as well as their mother and grandmother, who exhibited mild mental retardation. Other family members with negative genetic testing were normal. In silico analyses indicated that this missense mutation was predicted to reduce CASK protein stability, disrupt the SRC homology 3 (SH3) domain, and abolish its function. In summary, we identified a novel missense variate in CASK associated with MICPCH. Our work facilitates the diagnosis of the disease in this family and broadens the gene variant spectrum of the CASK in MICPCH patients.